Rancangan Model Pembelajaran Dick & Carey pada Materi Kalkulus Tingkat SMA - Salsabila Nando; Afrasiska Felisita Alus; Ulfah Hernaeny; Zanuar Renaldie (Yayasan Darussalam Bengkulu, 2024)
This article explains the development of the Dick & Carey learning design model for high school level Calculus material. The aim of this research is to explain the stages of development of Dick & Carey's learning design in designing effective and structured learning in the context of mathematics learning on Calculus material. The results of the development of Dick & Carey's learning design provide success in learning objectives. This learning model provides a systematic and structured stage process for teachers in making plans or designs for learning implementation. This learning model also emphasizes achieving certain learning objectives and evaluating learning outcomes. This article provides an overview of the importance of developing learning design models to achieve successful student learning activities.